2018
DOI: 10.1186/s12906-018-2339-x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of self-management exercise program with spa therapy for behavioral management of knee osteoarthritis: research protocol for a quasi-randomized controlled trial (GEET one)

Abstract: BackgroundOsteoarthritis (OA) is not limited to joint pain and stiffness, which can lead to disability; it is also linked to comorbidities such as overweight, obesity and fears and beliefs related to the pathology. The knee OA population appears more affected by these risk factors and has a lower physical activity (PA) level than the general population. The key challenge for OA treatment is increasing the PA level to decrease the risk factors.MethodsWe aim to perform a prospective, multicentric, quasi-randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
4
1
1
Order By: Relevance
“…Kao et al demonstrated that an SM program could improve the performance, health, and QOL of patients with KOA (46). The difference in the results of this study with other studies (12, 45, 46) was that the mentioned studies were conducted on male and female patients while the present study was carried out only among male patients.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Kao et al demonstrated that an SM program could improve the performance, health, and QOL of patients with KOA (46). The difference in the results of this study with other studies (12, 45, 46) was that the mentioned studies were conducted on male and female patients while the present study was carried out only among male patients.…”
Section: Discussioncontrasting
confidence: 57%
“…Mirzaee et al also showed that the implementation of an SM program in four sessions of 70 minutes for four weeks resulted in the improvement of the performance of elderly patients with KOA (12). Gay et al showed that an SM program could improve the physical activity of male and female patients with OA aged 50 - 75 (45). Kao et al demonstrated that an SM program could improve the performance, health, and QOL of patients with KOA (46).…”
Section: Discussionmentioning
confidence: 99%
“…This study was an ancillary study of Geet one study (NCT02598804) 14 which was conducted by Clermont-Ferrand University Hospital, from July 2015 to January 2017. Written consent was obtained after being informed of the aim of the study and before inclusion in the study.…”
Section: Methodsmentioning
confidence: 99%
“…A number of RCTs have used the IPAQ‐LF and the IPAQ‐SF to assess and classify the level of PA in a study population.…”
Section: International Physical Activity Questionnairementioning
confidence: 99%
“…Although the IPAQ questionnaire has been used in several RCTs, it was predominately designed for observational or population‐based studies. Several observational studies in MSK populations have used the IPAQ‐LF and the IPAQ‐SF .…”
Section: International Physical Activity Questionnairementioning
confidence: 99%